Entreprenurial orientation, strategic management accounting practices, innovation and firm performance: craft industry perspective / Nor Azlina Ab. Rahman, Aliza Ramli - Ab. Rahman, Nor Azlina; Ramli, Aliza (2014)
Globalization in new era changes business environment in various dimensions. Organizational integration factor, business strategy and innovation in technology were slowly becoming the major strategic issues which have significant impacts on organizations. The purpose of this paper is to scrutinize the issues coming in the way of small medium enterprises (SMEs) and firm performances within the craft industry development drawn on to the influence factors that enhances its performance, and to further provide an a framework to examine SMEs performances. Craft industry is a heritage industry which is considered as one of the major contributors in the manufacturing sector and also to the development of SMEs in most countries.However, it's potential is always underestimated. Relevant literature on entrepreneur, strategic management accounting practices, innovation and firm performance in SMEs within the craft industry are reviewed.In this paper, a framework of firm performance and factors affecting it is proposed that relies on resource-based view theory. A framework is developed to explore the premise for the research. Based on the suggested framework, entrepreneurial orientation, strategic management accounting and innovation are identified as factors affecting firm performance while the firm performance considers both financial and non-financial perspectives. The proposed framework allows the identification of the triggers driving SMEs performances and the capture of a holistic firm performance within the craft industry.